Milli-Interacting Dark Matter Interpretation of the Direct-Search Experiments - Quentin Wallemacq (Advances in High Energy Physics)
We reinterpret the results of the direct searches for dark matter in terms of milli-interacting dark particles. The model reproduces the positive results from DAMA/LIBRA and CoGeNT and is consistent with the absence of signal in the XENON100, CDMS-II/Ge, and LUX detectors. Dark atoms, interacting with standard atoms through a kinetic mixing between photons and dark photons and a mass mixing of σ mesons with dark scalars, diffuse elastically in terrestrial matter where they deposit all their energy. Reaching underground detectors through gravity at thermal energies, they form bound states with nuclei of the active medium by radiative capture, which causes the emission of photons that produce the observed signals. The parameter space of the model is explored and regions reproducing the results at the 2σ level are obtained for each experiment.